Artesunate and mefloquine in the treatment of uncomplicated multidrug-resistant hyperparasitaemic falciparum malaria. - Price, R; Luxemburger, C; van Vugt, M; Nosten, F; Kham, A; Simpson, J; Looareesuwan, S; Chongsuphajaisiddhi, T; White, N (1998)
Oral artesunate is the most effective treatment for uncomplicated hyperparasitaemia in falciparum malaria. To assess the contribution of mefloquine to therapeutic efficacy in an area endemic for mefloquine-resistant Plasmodium falciparum, an open randomized comparison of a 5 d course of oral artesunate (total dose 12 mg/kg) with and without a single dose of mefloquine (25 base mg/kg) was conducted in 100 adults and children with uncomplicated hyperparasitaemia (> 4% parasitized red blood cells). Both regimens were well tolerated and gave equally rapid clinical responses (84% of patients were aparasitaemic and 96% were afebrile within 48 h), but the recrudescence rate assessed at day 42 was 6% in those receiving artesunate with mefloquine compared to 36% in those receiving artesunate alone (adjusted hazard ratio 7, 95% confidence interval [95% CI] 2-32; P < 0.01). In addition, the efficacy of a 7 d course of artesunate, with and without the addition of mefloquine, was monitored in 178 patients who were not part of the randomized comparison. The failure rate was again lower in those receiving artesunate and mefloquine--7% (95% CI 2-13) compared with 26% (95% CI 8-44) in patients treated with artesunate alone. An oral regimen of 5 d or more of artesunate, together with mefloquine (25 mg/kg) given on day 2, is an effective treatment for uncomplicated hyperparasitaemic falciparum malaria in this area of high level multidrug resistance.